Niat untuk Berkunjung ke Destinasi Halal: Dampak Electronic Word of Mouth, Citra Destinasi Wisata, Sosial Media dan Perilaku Konsumen Citra Destinasi Wisata, Sosial Media dan Perilaku Konsumen - Handayani, Susi; Bismala, Lila; Hasibuan, Lailan Safina; Andriany, Dewi; Siregar, Gustina; Hafsah, Hafsah; Siregar, Hasan Sakti (BISNIS, 2024)
The intention to visit a halal destination is influenced by several factors, either directly or indirectly. The factors that influence intention to visit a halal destination include electronic word of mouth, destination image, social media and consumer behavior. The objectives of this study are (1) to examine the direct and partial effects of electronic word of mouth, destination image, social media on consumer behavior; (2) examining the direct and partial effects of electronic word of mouth, destination image and social media on intention to visit halal destinations; (3) examining the direct influence of consumer behavior on the intention to visit a halal destination; (4) examining the indirect influence between electronic word of mouth, destination image, social media on the intention to visit halal destinations mediated by consumer behavior. This study used path analysis with the SPSS program, with 73 research subjects.  The results showed that (1) partially, it was found that there was a significant influence between EWOM, destination image and social media on consumer behavior; (2) that E-WOM affects the intention to visit a halal destination, while consumer behavior, destination image and social media do not influence the intention to visit a halal destination; (3) consumer behavior shows a significant influence on the intention to visit a halal destination; (4) and from the analysis of the indirect effect, the results concluded that consumer behavior is not an intervening variable between E-WOM, destination image and social media.